Successful Surgical Management of a Rare Case of Mixed Type of Total Anomalous Pulmonary Venous Connection in a Very Low Birth Weight Preterm Child Using a Novel Surgical Technique. Issue 4 (July 2020) - Mehta, Anuj; Raju, Vijayakumar; Muthukumaran, Subramanian; Balakrishnan, Soundaravalli; Muthuswamy, Kalyanasundaram
We report a rare case of combined supra- and infracardiac type of total anomalous pulmonary venous connection (mixed-type TAPVC) in a 26-day-old low birth weight (1.9 kg) infant who was admitted with respiratory distress. The child underwent successful surgical repair using a novel surgical technique and is doing well at one year follow-up.